2009
DOI: 10.1164/rccm.200810-1558oc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Nurse-led Care for Symptomatic Moderate–Severe Obstructive Sleep Apnea

Abstract: A simplified nurse-led model of care has demonstrated noninferior results to physician-directed care in the management of symptomatic moderate-severe OSA, while being less costly. Clinical trial registered with http://www.anzctr.org.au (ACTRN012605000064606).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 38 publications
3
149
0
1
Order By: Relevance
“…[83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration). [83][84][85]110 This subset of studies will be referred to as "RCTs most generalizable to clinical practice" for the remainder of this discussion section.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[83][84][85][107][108][109][110] Four of these RCTs were determined to be most relevant to clinical practice, as they did not require oximetry testing as a criterion for inclusion and used conventional methods for determination of PAP pressures (i.e., APAP or attended titration). [83][84][85]110 This subset of studies will be referred to as "RCTs most generalizable to clinical practice" for the remainder of this discussion section.…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85][107][108][109][110] The meta-analysis showed a clinically and statistically insignificant difference of 0.38 points (95% CI: −1.07 to 0.32 points) greater improvement in patients randomized to the HSAT pathway versus the attended PSG pathway. This difference indicates that subjective sleepiness is similarly improved in patients who initiate PAP treatment based on diagnosis using either HSAT or PSG.…”
Section: Accuracymentioning
confidence: 99%
See 2 more Smart Citations
“…6 A report by the Sleep Health Foundation estimated the prevalence of OSA in Australia in 2010 was 4.7% or approximately 750,000 Australians. 1 A recent Australian community cohort study reported an OSA (AHI ≥ 10) prevalence of 53% in males age 40 y or older, and a moderate (AHI [20][21][22][23][24][25][26][27][28][29] to severe (AHI ≥ 30) OSA prevalence of 26%. 7 Comparable studies of indigenous peoples from New Zealand 8 and Canada 9 reported a Māori OSA prevalence of 14% (RDI ≥ 5), 11% (RDI ≥ 10) and 6% (RDI ≥ 15), and American Indian OSA prevalence of 33% (AHI [5][6][7][8][9][10][11][12][13][14] and 23% (AHI ≥ 15).…”
mentioning
confidence: 99%